Programa de capacitación “El manejo de residuos sólidos domésticos”, para el desarrollo buenas prácticas ambientales en los pobladores de segunda Jerusalén - Valdivia Lucana, Lidmam (2015)
Today the environment is considered as a complex system of interrelationships, since it is made up of connections between the different areas of the social system and the environment. In the final analysis, to speak today about the environment is not only deal with the dangers to the earth, the sea, the climate, flora and fauna. But it goes much further in trying to explain and analyze how originate from these hazards and disasters, and; what we can doto counteract oras there is not much. Through this research work is developing a training program called "The handling of domestic solid waste", as part of a non-formal education toa total of 162 residents of the neighborhood of SINAI - Second Jerusalem, Rioja Province, which represented our statistical sample; for which was conducted in coordination with the leaders of neighborhood, 03 training workshops 01 per month for 03 consecutive months, application of a questionnaire prior to the start of the program pre-test and at the end of the program Post Test. At the beginning of the implementation of the Training Program, Pre-test, the inhabitants of the neighborhood Sinai, had little interest in the good management of the residential solid waste, With a 48.1 % did not know that are the solid waste, only a 64.8 % gave him a high importance, the 60.5 % expresses its interest in participating in the training program, the 24.7 % - 21.6 % and 22.2 % did not know how to identify the type of waste to be deposited according to the color green, blue and yellow of the container respectively and 21% had the solid waste in the garbage truck municipal service. The program is finished the positive results were significant, falling to 1.9 % of th~ settlers who did not know that they were the solid waste, a 81.5 % gave high importance, 84% showed their interest in participating in the program and subsequent programs of training, the 87.5 % identified the type of waste and color of the container where deposit waste, as well as the 92.6% said they had been having their solid waste in the garbage truck municipal service. This knowledge variation (Coefficient of Variation) represents a 65.5 %, which demonstrates to us that the methodology used was a positive variability between the pre-test and post test, checking statistically the assimilation of the knowledge and skills (theoretical- practica!). Key words: domestic solid waste, Training Program.